Relationship Levels of Parent's Carefulness Iadvising Children With Sexual Behavior in Karya Village - Fithri, Nurhamida (Pena Cendekia Insani, 2024)
Background; Adolescence is a period of development in various aspects, including physical and psychosocial. Social problems caused by teenagers are not new but have existed for decades, one of which is the problem of deviant and worrying sexual behavior. These concerns can be addressed by the quality of the adolescent's parent-family relationship which instills correct concepts about behavior. This study aims to determine the relationship between the level of parental care in guiding children with adolescent sexual behavior in Karya Village. Method; . This type of research is quantitative with a cross-sectional approach. The sample in this study were 38 people who met the inclusion and exclusion criteria. Data collection techniques used primary data in the form of questionnaires distributed to respondents. Data processing used univariate and bivariate analysis. Results; The results of this study indicate that parental care has positive results. After doing bivariate analysis with chi square test obtained p-value of 0.012. Conclusion; The advice given is that it is recommended for parents to maintain good relationships with children so that children feel safe and comfortable at home, so that their roles and functions are felt by children.